Chimurenga war narratives, memory, trauma and the traditional psychiatric healing methods in Zimbabwe - Viriri, Advice (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
The article examines the connection between trauma and memory of Chimurenga War in Zimbabwean politics. It diagnoses how these Chimurenga War traumas “are inscribed and re-inscribed into everyday narratives. ”(.Edkins, 2003:15). It further dissects the traditional psychiatric healing systems vis-a-vis the serious needs of our times to protect African cultural diversity and traditional values, specifically modes of healing and compensation within families /communities in order to safeguard and promote the intangible cultural heritage for sustainable development. The country's statutory instruments silence and overshadow everyday practices, local level perspectives of justice and culturally sensitive methods of renovating impaired social relations. It goes on to propose the integration of traditional and conventional psychiatric practices because health is a phenomenon that can be shared inter-corporeally and intersubjectively both in this real world and even metaphysically. It is this very urgent and important task to safeguard a variety of intangible cultural heritage such as traditional psychiatric healing methods, rituals and customs, particularly this chosen rich and diverse medical care in Africa's culture.